Ethno-cultural traditions of the Iranians - Boranbayeva, A. Zh. (Journal of Oriental Studies, 2016)
The Iranian holidays as reflexions of the Iranian ethnic culture are considered by the author in this article. The author also analyses the similarities between Iranian and Kazakh customs and traditions.